Inequality of earnings and housing costs: Developments between and within regions - Philipp Breidenbach; Sandra Schaffner (Journal for Labour Market Research, 2025)
Household well-being is strongly influenced by changes in income - but real income is strongly determined by housing costs. The evolution of inequalities in both variables largely determines the development of living conditions between households. In this paper, we look at inequality trends between 2008 and 2017 from a regional perspective - between and within regions. While neighborhood earnings inequality has generally declined slightly, it is rising within Germany's largest cities. On the other hand, inequality in rents has less declined within those cities than in the rest of Germany, corresponding to price increases in poorer neighborhoods, too. Households in these poor neighborhoods thus suffer from a below-average earnings development, while it seems that the main costs caused by new rentals increase similar to the rest of the city.
Keywords: J31; R23; R31; 330; Inequality of earnings and housing costs; Regional disparities